Ultrasonic gas flow metering in hydrogen-mixed natural gas using Lamb waves - Shouhu Ji; Guanwei Jia; Weiqing Xu; Peiyu Zhang; Rui Li; Maolin Cai (AIP Advances, 2023)
Hydrogen mixing in existing natural gas pipelines efficiently achieves large-scale, long-distance, and low-cost hydrogen delivery. The physical properties of hydrogen and natural gas differ significantly. Hydrogen-mixed natural gas modifies the flow state and thermodynamic properties of the original natural gas in the pipeline. Hydrogen-mixed natural gas can lead to increased errors in ultrasonic flow metering because of the high sound speed and low density of hydrogen. Ultrasonic flowmeter installation distances need to be re-determined. In this study, a Lamb wave non-contact ultrasonic gas flow meter is used to measure the flow of hydrogen-mixed natural gas in a T-type pipeline. The greater the hydrogen mixing ratio, the higher the flow rate of the branch pipeline, and the shorter the installation distance of the ultrasonic flow meter, for example, 10% at 150D, 20% at 110D, and 30% at 20D. The time-difference method with high accuracy and broad applicability is used to calculate the flow rates of COMSOL simulated values. The errors between COMSOL simulation and theoretical flow rates at the shortest installation distance downstream do not exceed 3%. The errors at the position where the mixing uniformity is 80% are significantly higher than those at the shortest installation distance, and the maximum error is about 7.7%. The COMSOL simulation results show the feasibility and accuracy of ultrasonic gas flow metering of hydrogen-mixed natural gas.